E-Learning: Succeeding Amid the Pandemic Period, Forgotten in the Post-Pandemic Era - Bintang R. Simbolon; Hidayat Hidayat; Hartiningsih Hartiningsih; Cecep Wahyu Hoerudin; Imran Imran; Mia Aina (AL-ISHLAH: Jurnal Pendidikan, 2023)
As the coronavirus emerged, a necessity in the educational sector, instructors or lecturers have been required to establish teaching methodologies. On the other hand, as the epidemic winds down, the transmission of knowledge is gradually shifting back to being carried out offline or through a mixed approach. Online education is beginning to lose popularity as a result. This study aimed to examine the practical implications of knowledge gained through e-learning. Employing qualitative research by literature study, keywords used as data are mapped based on Google Scholar and Garuda sites in the form of books and articles are [“educational institutional”] and [“e-learning”] and [“pandemic”], by having ten inclusive data of literature associated with the intended subject matter. As a result, students felt more at ease and satisfied when using online learning as a platform for voicing their opinions and concerns. In addition, using various online learning media can facilitate an increase in the learner's level of autonomy. During the COVID-19 epidemic and the implementation phase, e-learning was particularly beneficial in online learning. Then, after it ends, learning with e-learning media is still very much needed because almost all educational institutions have optimally developed e-learning media along with improvements in implementation, always up to date with technological developments, and very effective and efficient by minimizing costs.